2020
DOI: 10.1371/journal.pone.0228449
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of diastolic dysfunction in patients with new and recurrent depression

Abstract: ObjectiveThe main objective of this study was to evidence the potential impact of the intensity, duration and recurrence of depression on the development of arterial stiffness (AS) leading to left ventricular hypertrophy (LVH) and diastolic dysfunction (DD) in patients with new onset depression (NOD) and recurrent depression (RD) in comparison to 33 control subjects without depression. Another aim was to identify potential predictive factors regarding the occurrence of diastolic dysfunction (DD). MethodsOur st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…ANS imbalance is associated with major depression, and alterations of HRV and HRT were frequently evidenced for this patient category in various medical studies [25][26][27]. It seems that the amplitude of HRV reduction matches the severity of depressive symptoms.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…ANS imbalance is associated with major depression, and alterations of HRV and HRT were frequently evidenced for this patient category in various medical studies [25][26][27]. It seems that the amplitude of HRV reduction matches the severity of depressive symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…Data regarding the reversibility of HRV and HRT alterations under therapy with antidepressants are not entirely conclusive, with some studies evidencing further reductions of HRV during treatment. Nevertheless, in the case of SSRI therapy, notable improvements were evidenced in multiple studies [25][26][27][28]. However, we have highlighted the importance of early detection of mental health difficulties, when aiming to prevent and even treat CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Several findings evidenced a reduced HRV and cardiovascular diseases association, as expressed by lower values in the time-domain, in patients that are suffering from depression compared to healthy controls [ 50 , 51 , 52 , 53 ]. A meta-analysis based on 36 articles [ 54 ] showed that anxiety disorders are associated with lower HRV values.…”
Section: Discussionmentioning
confidence: 99%
“…An adequate ToM, alongside neurocognition, ensures a good social functioning and adequate interpersonal relationships. 10 Recurrent depressive episodes are known to have an overabundance of critical negative consequences, not only impacting the physical health in various ways, 21 but also progressively leading to cognitive dysfunctions, which are detrimental to social functioning. 22 Certain clinical trials involving patients with chronic depressive disorders have shown an impairment in cognitive functioning, as well as emotional processing deficits/empathy that include ToM.…”
Section: Introductionmentioning
confidence: 99%